Effect of interval running training on the results of running 800 meters students of university of suryakancana - Muhamad Guntur Gaos; Muhamad Arifin (Universitas Suryakancana, 2025)
This study aims to determine the effect of interval training on the results of running 800 meters. This study used an experimental method with the treatment variable of interval running, while the bound variable was 800-meter running. The research sample of 23 Penjas students was taken by stratified random sampling through the matching paired technique. The processing of this hypothesis test uses a paired samples test. The hypothesis is accepted if the significance value is less than alpha (with an alpha of 0.05). From the data above, the significance value for the experimental pretest and post-test data is 0.00 which means that the hypothesis is accepted. Likewise, the pretest and post-test data of the control group was 0.003, which means that the hypothesis was accepted.The results of this study conclude that interval training has an effect on the outcome of running 800 meters or in other words there is a significant influence of interval training on the outcome of running 800 meters.The focus of development carried out by the researcher is more focused on the strength of training to improve the ability to run 800 meters, where these endurance, speed and strength factors are very useful in improving the overall physical condition. Some of the reasons why endurance, speed and strength are very important in improving overall physical condition because they are the driving force in every physical activity, especially athletes. Strength also plays a very important role in protecting and minimizing sports practitioners, especially athletes, from the possibility of injuries that can hinder the athlete's own achievement.